Asymmetric transformation of achiral gold nanoclusters with negative nonlinear dependence between chiroptical activity and enantiomeric excess - Chang Liu; Yan Zhao; Tai-Song Zhang; Cheng-Bo Tao; Wenwen Fei; Sheng Zhang; Man-Bo Li (Nature Communications, 2023)
Abstract The investigation of chirality at the nanoscale is important to bridge the gap between molecular and macroscopic chirality. Atomically precise metal nanoclusters provide an ideal platform for this research, while their enantiopure preparation poses a challenge. Here, we describe an efficient approach to enantiopure metal nanoclusters via asymmetric transformation, that is, achiral Au23(SC6H11)16 nanoclusters are converted into chiral and enantiopure Au24(L)2(SC6H11)16 nanoclusters by a chiral inducer phosphoramidite (L). Two enantiomers of Au24(L)2(SC6H11)16 are obtained and the crystal structures reveal their hierarchical chirality, which originates from the two introduced chiral L molecules, the transformation-triggered asymmetric rearrangement of the staple motifs on the surface of the gold core, and the helical arrangement of nanocluster molecules. The construction of this type of enantiomerically pure nanoclusters is achieved based on the easy-to-synthesize and modular L. Lastly, the chirality-related chiroptical performance was investigated, revealing a negative nonlinear CD-ee dependence.